Framing of the North American Free Trade Agreement (NAFTA) in the Opinion Published by the Mexican Press: The First Four Months of Trump - Azpíroz, María Luisa (Estudios sobre el Mensaje Periodístico, 2018)
One of the promises of Donald Trump’s election campaign was the renegotiation of the North American Free Trade Agreement (NAFTA), signed in 1994 by the United States, Canada and Mexico. Since Trump has been in office, has the Mexican press reflected the concerns and prospects that renegotiating NAFTA would have for the country? This could be verified with an analysis of the pieces of opinion, in which different authors can offer their interpretation without the constraints of objectivity and impartiality. This article, using framing and rhetorical criticism as a methodological basis, offers an analysis of the opinion pieces about NAFTA that were published in two Mexican newspapers (El Universal and Reforma) during the first four months of Donald Trump’s government.